Validity of the online athlete management system to assess training load - Menaspà, M. J.; Menaspà, P.; Clark, S. A.; Fanchini, M. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To validate the quantification of training load (session rating of perceived exertion [s-RPE]) in an Australian Olympic squad (women`s water polo), assessed with the use of a modified RPE scale collected via a newly developed online system (athlete management system). Methods: Sixteen elite women water polo players (age=26 [3] y, height=1.78 [0.05] m, and body mass=75.5 [7.1] kg) participated in the study. Thirty training sessions were monitored for a total of 303 individual sessions. Heart rate was recorded during training sessions using continuous heart-rate telemetry. Participants were asked to rate the intensity of the training sessions on the athlete management system RPE scale, using an online application within 30 min of completion of the sessions. Individual relationships between s-RPE and both Banister training impulse (TRIMP) and Edwards` method were analyzed. Results: Individual correlations with s-RPE ranged between r=.51 and .79 (Banister TRIMP) and r=.54 and .83 (Edwards` method). The percentages of moderate and large correlation were 81% and 19% between s-RPE method and Banister TRIMP, and 56% and 44% between s-RPE and Edwards` method. Conclusions: The online athlete management system for assessing s-RPE was shown to be a valid indicator of internal training load and can be used in elite sport.